2022
DOI: 10.1097/njh.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

“I Didn't Want My Baby to Pass, But I Didn't Want Him Suffering Either”

Abstract: Little is known about how nursing care at the end of a child's life impacts long-term parental bereavement. We aimed to explain, contextualize, and examine comparisons between quantitative trends in children's end-of-life care and parents' qualitative perceptions. We used a mixed methods design, combining quantitative data from the RESTORE clinical trial with qualitative interviews with bereaved parents. Patients who died during RESTORE were included in quantitative analyses. A subset of their parents was inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…25 Research among caregivers of adults with advanced cancer suggests that high-quality EOL care with attention to symptoms and suffering may reduce the risk of bereavement regret. 8 In pediatrics, the uniquely interdependent role of parent and child complicates assessment of EOL suffering, [34][35][36][37] requiring a collaborative approach to care. Enhancing care by strengthening support for mothers, incorporating routine parental assessment of child symptoms and suffering, and responding accordingly throughout treatment and especially at the EOL may help buffer against decisional regret.…”
Section: Discussionmentioning
confidence: 99%
“…25 Research among caregivers of adults with advanced cancer suggests that high-quality EOL care with attention to symptoms and suffering may reduce the risk of bereavement regret. 8 In pediatrics, the uniquely interdependent role of parent and child complicates assessment of EOL suffering, [34][35][36][37] requiring a collaborative approach to care. Enhancing care by strengthening support for mothers, incorporating routine parental assessment of child symptoms and suffering, and responding accordingly throughout treatment and especially at the EOL may help buffer against decisional regret.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring what matters during EOL care for children is complex and requires incorporating multiple, at times divergent, perspectives. Recent research demonstrated that while clinicians’ documented comfort scores may indicate that patients were relatively pain-free at EOL, parents recount their child’s suffering years later (35, 36), suggesting clinicians may underestimate symptoms. Measures such as the QODD may capture the breadth of PCICU EOL experiences better than existing documentation or quality metrics.…”
Section: Discussionmentioning
confidence: 99%